Closely spaced dual-wavelength fiber laser using an ultranarrow bandwidth optical filter for low radio frequency generation - Ahmad, Harith; Razak, N.F.; Zulkifli, M.Z.; Muhammad, F.D.; Munajat, Y.; Harun, Sulaiman Wadi (Optical Society of America, 2014)
A dual-wavelength (DW) fiber laser with a closely spaced single longitudinal mode (SLM) output is proposed and demonstrated. The proposed fiber laser utilizes a conventional fiber Bragg grating with a center wavelength of about 1546.8 nm in conjunction with an ultranarrow bandwidth tunable optical filter to generate the desired DW SLM output. Observations with a very high resolution optical spectrum analyzer, which was capable of achieving resolutions up to 0.16 pm, revealed detailed spectral characteristics not characteristically seen before. A channel spacing of up to 58 nm was realized, and spacing as small as 2 pm was achieved. The minimum channel spacing and its resulting beat frequency are the narrowest observed yet to the best of our knowledge for a DW fiber laser at room temperature.